Detectorists : movie special [videorecording (DVD)] - Crook, Mackenzie, 1971-; Crook, Mackenzie, 1971-; Jones, Toby, 1966-; Weyland, Matt; Stirling, Rachael, 1977-; Wallace, Asa; Horan, Gerard; Quigley, Pearce; Checkley, Laura; Thompson, Sophie, 1962-; Ladwa, Divian; Ben, Orion; et al. (RLJ Entertainment, 2023)
The Danebury Metal Detecting Club is in trouble; developers are sniffing around, and after losing out on a big finder's fee, the club is going to need a miracle to help save their beloved scout hall.